IJCM_325A: A Study on Relationship of Working Status of Rural Adult Women with Their Mental Health in a Rural Block of West-Bengal - Sur Aditi; Paul Bobby; Bandyopadhyay Lina; Sahu Monalisha; Basu Rivu (Wolters Kluwer Medknow Publications, 2024)
Background: Mental health is a major public health concern worldwide. Studies showed that women are impacted at a higher rate than men. There is definite scarcity of studies in public health domain, which reflect the mental health and its correlates among rural women specially in relation to their working status. Objectives: Present study envisages to assess and compare the mental health status of working and non-working adult rural women and find out the factors associated with the mental health status of the study participants. Methodology: A community based; cross-sectional study was done between August 2023 to November 2023 in a rural area of Hooghly district. The sample consists of 394 women (197 working women and 197 non-working women) were selected using Multistage random sampling from 3 villages. Using the predesigned, pretested interview schedule and self-reporting questionnaire, all relevant information was collected. The collected data was analysed using descriptive and inferential statistics using SPSS 16 version. Institutional Ethics Committee clearance was obtained. Results: The mean age of the study participants was 37 (± 10.09) years. Most of them belonged to socio-economic class IV. Majority of them were currently married. Around 22.33% of working women and 28.40% of non- working women had poor mental health. The factors associated with poor mental health among working women were work place atmosphere (p<0.01), attitude of colleagues (p=0.01), attitude of family members (p=0.01), social support satisfaction (p<0.01) and the factors associated with poor mental health among non-working women were satisfaction status of getting financial aid from family members (p=0.016), domestic violence (p<0.01). Conclusion: Awareness program regarding various aspects of mental health for both working and non-working women at family level, community level as well as at workplace could be a useful strategy in reducing this public health problem.